An assessment of the quality of reference service at the University of the Philippines Diliman Main Library - Sabat, Elizabeth M. (2000)
The study took into consideration the total environment of references services with the reference librarian as the center of reference desk operations; hence the evaluation was focused on the primary activity of which is personal assistance provided by library staff to users in pursuit of information.